Cardiopathy and chronic renal failure in a diabetic patient - Sonia Regina Jurado, Vitor Pereira Machado (ARCHIVES OF HEALTH INVESTIGATION, 2019)
Introduction: The type 2 of diabetes mellitus (DM) is a chronic metabolic disorder characterized by insulin resistance and hyperglycemia. It is associated with long-term complications, such as cardiovascular diseases, nephropathy, retinopathy, and other kind of tissue damage and dysfuction. Objective: The present case aims to illustrate the association between diabetes and arterial hypertension, contributing to the genesis of renal dysfunction. Clinical case: M.H, 59 years old, female, married and housewife. Patient had a 29 year history of type 2 diabetes, hypertension and left ventricular hypertrophy, diabetic retinopathy 4 years previously, chronic kidney disease due to diabetic nephropathy and right diabetic foot with double-digit amputation. For the past 9 months, she had been undergoing hemodialysis 3 times weekly for 4 hours each time via a left arm arteriovenous fistula. The patient’s medications included oral hypoglycemic and antihypertensive. She was admitted to hospital emergency in the city of Três Lagoas, State of Mato Grosso do Sul, Brazil, presenting the following complaints: hypotension, hypervolemia, dysponea, dizziness and astenia. Ten days after admission, the patient died due to hydroelectrolytic disturbance, systemic arterial hypertension, chronic renal failure and diabetes mellitus. Results: Glycemia: 269 mg/dl; potassium: 6.4 mmol/l; sodium: 140 mEq/l; calcium: 9.1 mg/dl; magnesium: 2.3 mg/dl; chlorine: 103 mEq/l; creatinine: 5.3 mg/dl; albumin: 2.7 g/dl and urea: 171 mg/dl. Ultrasonography of the abdomen showed both kidneys with a normal form. Chest x-ray revealed increased cardiac area and thickened bronchial weave in both lungs. Electrocardiogram: sinus rhythm and left ventricular overload. Echocardiogram: 26 mm aorta, right ventricle measuring 22 mm, left ventricle measuring 68 mm in diastole and 56 mm in systole, ventricular function with ejection fraction of 0.37 and systolic fraction of 0.18, interventricular septum with 10 mm of thickness and decreased movement, tricuspid valve with discrete insufficiency, mitral valve with moderate insufficiency; normal pulmonary and aortic valves and pericardium with discrete effusion. Conclusion: In this study, the patient had diabetes for almost 30 years and did not adequately control blood glucose, which contributed to the development of hypertension and late detection of heart disease and chronic renal failure due to diabetes. Descritores: Hipertensão Arterial; Diabetes; Hemodiálise.